The implications of various seed priming treatments on seed yield in proso millet (Panicum miliaceum) - NARAYANAN, G SATHIYA; ARUNKUMAR, S; VENKATAKRISHNAN, D; BALAJI, D S (The Indian Journal of Agricultural Sciences, 2024)
The experiment was conducted during rainy (kharif) season of 2021 and winter (rabi) season of 2022 at Annamalai University, Annamalai Nagar, Chidambaram, Tamil Nadu to identify suitable seed priming technique, soaking duration and priming agents for halo, osmo, and bio-priming in proso millet (Panicum miliaceum L.). To increase crop yield and sustainability in present-day agriculture, seed priming continues to be essential by utilizing scientific knowledge and technical breakthroughs. The experiment was laid out in factorial completely randomized design (FCRD) with three replications. The fresh seeds of proso millet cv. CO4 were imposed for halo, osmo, and bio priming treatments, viz. Agent for halo-priming: Control, hydropriming, KH2PO4 (1 and 2%), ZnSO4 (1 and 2%), and CaCl2 (1 and 2%); Agent for osmo-priming: Control, hydropriming, NaCl (1 and 2%), Mannitol (1 and 2%), and PEG (-10 and -15 Bar); Agent for bio-priming: Control, hydropriming, Azospirillum (15 and 20%), P. fluorescens (LF) (10 and 15%), Prosophis LE (5 and 10%), and soaked in equal volumes for 6 and 8 h. The results revealed that for halo priming, seeds soaked in 2% KH2PO4 for 8 h; for osmo priming seeds soaked in 2% mannitol for 8 h and for bio-priming seeds soaked in 15% P. fluorescens (LF) for 8 h outperformed other treatments. Field experiments were also conducted to determine the productivity of seed primed proso millet. The results showed that the crop performance was superior in seeds primed with 2% KH2PO4 for 8 h during kharif season than rabi.